'Feeling more like a mechanic' - A qualitative study on experiences of caries prevention to patients with recurrent cavities among experienced dentists - Karin Sunnegårdh-Grönberg; Jenny Molin; Håkan Flink; Britt- Marie Lindgren (Medical Journals Sweden, 2024)
Objective: To explore experiences of caries prevention in adult patients with recurrent cavities among experienced dentists.  Method: Five focus group discussions consisting of seven men and nine women, 38-61 years of age, and with working experience as dentists between 5 and 35 years, were conducted. The participants represented Public Dental Health Service clinics and private practitioners. Qualitative content analysis was used to analyze data.  Results: The participants emphasized the importance of effective communication and patient engagement in caries prevention. They described their experiences as an endless trail, making fillings. They expressed their inability to take necessary responsibility and being stuck in the dental care system due to various circumstances. The understanding of caries was contradictory, and an inadequate mandate to control time to fulfill their preventive work was evident. They felt responsible to do the best for their patients, but how to share responsibility with colleagues and patients and having enough time for this seemed difficult and unclear. These problems did not motivate to further education in cariology. Conclusion: The findings underscore the urgent need for improvement in preventive caries treatment and the necessity of allocating sufficient time for dentists to engage in this crucial aspect of their work.